BENTUK KALIMAT DAN FUNGSI TINDAK TUTUR EKSPRESIF DALAM NOVEL CRTITICAL ELEVEN - Reisti Reisti; Ike Revita; Aslinda Aslinda (Universitas Muhammadiyah Tapanuli Selatan, 2021)
This study aims to describe the form and function of expressive speech acts in Novel Critical Eleven by using expressive speech act theory. The object of this research is the form of expressive speech contained in the novel Critical Eleven and classified by type and function based on the context of the speech. The method in this study used a qualitative descriptive approach with the free-involved-talk (SLBC) technique. The results showed that there were 40 (forty) data regarding expressive speech acts in the novel Critical Eleven. The function of speech acts contained in this novel is a function that is adapted to the context of the ongoing speech, namely the function to express apologies, complain, praise, regret, congratulations, thank you, disappointed, ask, longing, ask for help, attention, request, invites, jokes, hopes, commands, and sympathy.